(untitled) (Colombia Medica, 2007)
Objective: To evaluate the immunogenicity of Hepavax-Gene recombinant hepatitis B vaccine in INML workers since the last administered doses. Methods: Cross-sectional study on 603 health workers with at least three administered recombinant vaccine doses. Antibody levels (anti-HBs) were measured using the ELISA technique during December 2000 and January 2001, taking into account that the last dose in the vaccination varied between 1 and 6 years. Results: A total of 344 men and 259 women with an age mean of 38.8±7.3 years were studied. Protection levels were found in 90.7% (>10 U/l), decreasing significantly with the worker’s age (p< 0.001) and with the vaccine last dose administration time (p< 0.01). Health workers with four doses compared to those with three doses had a 4.7% higher protection (antibody median 209.8 vs. 130.07, p< 0.001). No association was found with gender (p=0.463), smoking (p=0.331) and blood exposure (p=0.433). Multivariate analyses found that no protection associated only with age (40-44 years HR=2.37, CI 95%:1.18,4.78 and >45 years HR=3.58, CI 95%: 1.83,6.99). Conclusions: Although Hepavax-Gene recombinant hepatitis B vaccine (anti-HBs) has a high effectiveness in the health workers (90.7%) it presents a decrease in protection levels related to a higher worker’s age and a long vaccine last dose administration time.